STUDENTS’ PERCEPTIONS ABOUT THE IMPLEMENTATION OF PEER-ASSISTED REFLECTION LEARNING IN MULTIVARIABLE CALCULUS LECTURES - Isra Nurmai Yenti; Yaya S. Kusumah; Jarnawi Afghani Dahlan (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
A large class can be a problem source in learning Calculus. Peer-Assisted Reflection learning,as the solution, is a learning that combines peer analysis and self-reflection. The purpose of this study was to describe the implementation of Peer-Assisted Reflection learning based on Students’ opinions in Multivariable Calculus lecture. The research design used was pre-experimental with a one-shot case study design. The data obtained from questionnaire responses were analyzed by using descriptive statistics. The result of this study shows that thePeer-Assisted Reflection learning help Students’s carry out activities: reflecting the result of their own work, commenting on the friend’s work, and increasing understanding of the material after revising their work. On contrary, the Peer-Assisted Reflection learning has not been able to carry out the following activities: determining concepts, understanding problems in a short time, understanding the work of colleagues, and finding doubts about the correctness of the answers.